Graduate student use of a multi-slate reading system - Chen, Nicholas; Guimbretiere, Francois; Sellen, Abigail (Proceedings of the 2013 SIGCHI Conference on Human Factors in Computing Systems (CHI 2013), 2013)
In laboratory studies, multi-surface slate-based reading systems have shown great promise as platforms for active reading. However, the true utility of such a system can only be ascertained through the rigors of real world use. We conducted month-long deployments of a multi-slate reading system to support the active reading activities of graduate students in the humanities. During these deployments we documented how the added display area and increased micro-mobility of multiple devices enhanced navigation and reading comfort. We also noted the essential role of writing and annotation. Finally, we observed how electronic affordances like synchronization across devices helped provide functionality that would not have been possible with paper documents. This paper contributes new information about how electronic reading solutions fit into real world reading workflows.